Gaya Komunikasi Dakwah Ustadz Handy Bonny dalam Membina Spirit Hijrah Anak Muda - Miftachul Aula; Sutamaji (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2025)
This study aims to examine in depth the rhetorical strategies employed by Ustadz Handy Bonny in fostering the spirit of hijrah (spiritual migration) among youth through the Endikat Teman Hijrah community in Bandung. The growing hijrah phenomenon among young people highlights the need for a da'wah approach that is adaptive, communicative, and aligned with contemporary youth culture and lifestyle. This research uses a qualitative method with a case study approach, utilizing in-depth interviews, participatory observation, and documentation as data collection techniques. The findings reveal that Ustadz Handy Bonny successfully established effective da'wah communication through the use of casual language, popular diction, structured message delivery, and emotional engagement with the audience. The Endikat Teman Hijrah community serves as a supportive social space for the spiritual transformation of youth through a variety of religious and social activities presented in an engaging and relatable manner. The rhetorical approach applied by Ustadz Handy Bonny not only captures attention but also inspires behavioral and attitudinal change, particularly in cultivating a collective spirit of hijrah among young people. This study recommends the enhancement of rhetorical competencies among preachers to ensure that da'wah messages are more acceptable, understandable, and internalized by the younger generation.